2009
DOI: 10.22358/jafs/66388/2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E and selenium supplementation on haematology, blood chemistry and thyroid hormones in male buffalo (<i>Bubalus bubalis</i>) calves

Abstract: An experiment was conducted on 20 male buffalo calves (average body weight 75.30 ± 2.20 kg) to elucidate the effect of supplemental vitamin E and/or selenium (Se) on their haematology, blood metabolic profi le, serum enzymes and thyroid hormones status. Group I served as control (without any supplementation), groups II, III and IV were supplemented with 0.3 mg Se, 300 IU of DL-α-tocopheryl acetate, and both 300 IU DL-α-tocopheryl acetate and 0.3 mg Se, respectively. Animals were fed on wheat straw and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
11
21
1
Order By: Relevance
“…The mean haemoglobin (Hb) values (8.9 to 9.3 g/dl) and PCV (27.9 to 28.5 %) values were in normal range and were found to be comparable (P>0.05) in all the three groups. Similar findings was observed by Shinde et al (2009) in buffalo calves who observed that supplementation of selenium and vitamin E had no effect on the haematological parameters viz., Hb and PCV. Contrary to the above findings, Qureshi et al (2001) reported significantly (P<0.05) higher haemoglobin concentration and PCV values in buffaloes supplemented with selenium.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The mean haemoglobin (Hb) values (8.9 to 9.3 g/dl) and PCV (27.9 to 28.5 %) values were in normal range and were found to be comparable (P>0.05) in all the three groups. Similar findings was observed by Shinde et al (2009) in buffalo calves who observed that supplementation of selenium and vitamin E had no effect on the haematological parameters viz., Hb and PCV. Contrary to the above findings, Qureshi et al (2001) reported significantly (P<0.05) higher haemoglobin concentration and PCV values in buffaloes supplemented with selenium.…”
Section: Resultssupporting
confidence: 87%
“…Similarly Arthur et al (1988) did not observe any effect of supplementation of Se on the serum total protein and albumin levels of Friesian steers. Similarly Shinde et al (2009) observed that supplementation of either Se (0.3 ppm) or vitamin E (300 IU) or both (300 IU vitamin E and 0.3 ppm Se) in the diet had no effect on serum albumin, globulin and albumin: globulin ratio (P>0.05) in buffalo calves. The mean values of total cholesterol, although numerically higher in Se supplemented groups (108.4 mg/dl) as compared to control (103.4 mg/dl), but did not reveal any statistical (P>0.05) differences.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Increased T 3 concentration can be explained by increased activity of enzyme type 4 deiodinase in the conversion of thyroxine T 4 into the more active triiodothyronine T 3 and is in positive correlation with energy and nitrogen balance ration. Shinde et al (2009) showed significantly higher activity of T 3 hormone in the blood of buffalo calves that were fed with the addition of Se (sodium selenite), compared to those without added Se. Similarly Nayyar et al (2003) also reported that buffalo heifers that were supplemented with Se had significantly (P < 0.05) higher T 3 concentrations compared to unsupplemented control animals.…”
Section: Thyroid Hormonesmentioning
confidence: 99%